Effects of physically active lessons and active breaks on cognitive performance and health indicators in elementary school children: a cluster randomized trial - João Carlos N. Melo; Julian Tejada; Ellen Caroline M. Silva; José Ywgne; David N. Oliveira; Larissa Gandarela; Danilo R. Silva (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background This cluster‐randomized trial examined the effects of active breaks (AB) and physically active lessons (PAL) on cognitive function and health indicators in elementary school children. Methods Six schools were randomly assigned to three groups: AB group (n = 61), PAL group (n = 77), and a control group (CTL, n = 46). First-year elementary school students participated (6.9 ± 0.6 years; 52.7% girls), and the interventions lasted eight weeks. Cognitive function was measured via reaction time and correct responses on computerized tests (Go/NoGo, DigitSpan, Mental Rotation, Visual Search, and Cueing Posner). Secondary outcomes included physical activity, quality of life, daytime sleepiness, and school perception. Results Significant group-by-time interactions were found in four tests: Go/NoGo (reaction time: p = 0.045), DigitSpan (correct responses: p = 0.020), Mental Rotation (reaction time: p = 0.049), and Cueing Posner (reaction time: p = 0.017). Only the PAL group presented a reduction in reaction time in inhibitory control (Go/NoGo) (change from baseline [Δ] = -106.4 ms; p < 0.001; d = 0.50), with a greater reduction than the AB group (difference-in-differences [DiD] = -107.3 ms; p = 0.019; d = 0.47). Short-term memory (Digit Span) improved only in the PAL group (Δ =  + 0.6; p < 0.001; d = 0.44), with larger gains than the CTL group (DiD =  + 0.7; p = 0.024; d = 0.54) and AB group (DiD =  + 0.7; p = 0.010; d = 0.49). Spatial reasoning (Mental Rotation) improved in both the PAL (Δ = -1967.5 ms; p < 0.001; d = 0.72) and AB groups (Δ = -1477.8 ms; p < 0.001; d = 0.54), but only the PAL group showed a greater change than the CTL group (DiD = -1394.0 ms; p = 0.012; d = 0.54). Spatial orientation (Posner Cueing) improved in all groups (PAL group: Δ = -386.6 ms; p < 0.001; d = 0.68; CTL group: Δ = -183.8 ms; p = 0.024; d = 0.29; AB group: Δ = -158.4 ms; p = 0.007; d = 0.36), with the PAL group presenting greater reductions than the CTL (DiD = -202.8 ms; p = 0.045; d = 0.33) and AB groups (DiD = -228.2 ms; p = 0.007; d = 0.45). Conclusions Physically active lessons enhanced various cognitive functions, while active breaks, although less impactful, also represent a beneficial strategy. Trial registration Brazilian Clinical Trials Registry (REBEC trial: RBR-10zxwdrh, retrospectively registered on 2025-01-09, https://ensaiosclinicos.gov.br/rg/RBR-10zxwdrh ).